2022
DOI: 10.5194/gmd-15-6759-2022
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of four algorithms for detecting tropical cyclones using ERA5

Abstract: Abstract. The assessment of tropical cyclone (TC) statistics requires the direct, objective, and automatic detection and tracking of TCs in reanalyses and model simulations. Research groups have independently developed numerous algorithms during recent decades in order to answer that need. Today, there is a large number of trackers that aim to detect the positions of TCs in gridded datasets. The questions we ask here are the following: does the choice of tracker impact the climatology obtained? And, if it does… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Simulated TCs were objectively tracked in the EC‐Earth3P, CMCC‐CM2, and HadGEM3‐GC3.1 models. Objectively tracked TCs are sensitive to the choice of tracking algorithm, as well as the metrics used within the trackers (Bourdin et al., 2022; Zarzycki & Ullrich, 2017). Intensity thresholds in particular have been shown to drive differences in TC frequencies between trackers (Horn et al., 2014).…”
Section: Models and Methodsmentioning
confidence: 99%
“…Simulated TCs were objectively tracked in the EC‐Earth3P, CMCC‐CM2, and HadGEM3‐GC3.1 models. Objectively tracked TCs are sensitive to the choice of tracking algorithm, as well as the metrics used within the trackers (Bourdin et al., 2022; Zarzycki & Ullrich, 2017). Intensity thresholds in particular have been shown to drive differences in TC frequencies between trackers (Horn et al., 2014).…”
Section: Models and Methodsmentioning
confidence: 99%
“…All models reasonably reproduce the spatial pattern and seasonality of cyclone genesis. There are significant biases in the total yearly number of detected TCs (Bourdin et al., 2022). However, that is not an issue for the sake of comparison with GPIs as those indices by construction only describe variations of cyclone number and not its absolute value.…”
Section: Methodsmentioning
confidence: 99%
“…To provide a fair comparison with the deterministic TC trackers, the same IBTrACS data set including ET cyclones was used. This required using the Subtropical Jet Cut-off post-treatment method described in Bourdin et al (2022) to filter out ET cyclones. We found that the POD value is almost identical to most of the deterministic trackers compared, while the FAR value is in-line (but slightly higher) with two of the trackers considered (OWZ and TRACK).…”
Section: Hybrid Tracking Scheme Skillsmentioning
confidence: 99%